Investigating the Causes of Poor Cost Control in Iraqi Construction Projects - Abbas, N. N.; Burhan, A. M. (Engineering, Technology & Applied Science Research, 2022)
Controlling cost in construction projects is an essential issue. This study investigates the most critical problems that cause weakness in cost control in Iraqi construction projects. The quantitative technique was used by conducting a survey directed to professionals who work on construction projects. One hundred and sixty-four questionnaire forms were distributed to private sector companies, government companies, and government institutions, and the responses were subjected to the required statistical analysis. The results indicate that the most influential factors are the weakness in keeping up with the use of modern concepts, methods, and technologies, the delay in receiving the amounts due for work done from the owner, fluctuations in market prices, the lack of knowledge and the inefficient use of currently available tools and technology, and the security situation in the country. The results indicate that the Iraqi construction projects suffer from weakness in cost control, which causes them to stop or delay their delivery, and this needs serious and quick solutions. One of the most important solutions is the adoption of modern technologies and their inclusion in the construction sector and the development of special systems for managing costs that are appropriate to the Iraqi construction environment.